A practical model for e-commerce adoption in Iran. Issue 6 (23rd August 2014) - Hajli, Nick; Sims, Julian; Shanmugam, Mohana
Abstract : Purpose: Developing countries are still challenged by infrastructural and cultural issues related to the adoption of e-commerce although with the emergence of social commerce, a new stream has been introduced. Iran is a developing country, in which the adoption of e-commerce by SMEs is challenged by such barriers; it is now applying models for the adoption of new technologies by SMEs. Design/methodology/approach: This research attempts to develop a model, based on existing models of e-commerce, which can be applied in Iranian conditions. The study uses data gathered by a survey, together with existing models in this area, in order to propose a new model, which has been empirically tested. Findings: The results of this research demonstrate that e-commerce barriers in Iran are related to a lack of awareness of the benefits of e-commerce adoption, as well as organisational issues related to its application. The paper also discusses the results and implications of this research, which can be applied to other developing countries. The paper also gives a better picture of Iranian market. Finally the paper discusses possible future directions of this research, as well as its limitations. Originality/value: This study contributes to the theoretical basis of IS and e-commerce adoption studies by proposing and testing a pre-adoption model for e-commerce. The adoption of e-commerce in SMEs in Iran has not been substantially investigated. This is despite the fact that SMEs play an important role in all economies. The results demonstrate a significant relationship between organisational readiness and the adoption of e-commerce. It also shows that there is a positive relationship between awareness of e-commerce and its adoption.